Edukasi Hukum Bagi Peserta Didik SMK Fadilah Tangerang Selatan Dalam Upaya Pencegahan Dan Penanggulangan Cyberstalking Dan Cyberbullying di Kalangan Pelajar - Adi Nur Rohman; Sugeng (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2022)
Cyberstalking and cyberbullying are one of the latentimpacts of such rapid technological advances. The emergence ofvarious social media that is not matched by the ability to use themcreates loopholes for the transformation of crimes such asstalking and bullying. So far, the act of stalking and bullying viasocial networks in Indonesia is still considered a trivial mattereven though it actually has a very serious impact on a person'spsychological development and especially among teenagers. Thepartner of this service activity is Fadilah Vocational Schoolwhich is located in the South Tangerang area. Among theproblems faced by partners is the lack of knowledge regardingthe types and impacts caused by cyberstalking and cyberbullying.In addition, partners are also faced with the problem of their lackof understanding regarding cyber legal aspects of cyberstalkingand cyberbullying. This service activity offers solutions in theform of seminars and education on concepts and regulationsrelated to cyber law and information technology, with the outputof increasing participants' understanding regardingidentification, prevention and overcoming of cyberstalking andcyberbullying. The second solution is to provide assistance forstudents to be able to better understand directly the material thathas been delivered.